Preparation method of atorvastatin calcium tablet

Through the composite, dry granulation and electrostatic coating technology of nano-scale raw materials and sustained-release microspheres, atorvastatin calcium tablets were prepared, which solved the problems of slow drug dissolution rate and poor stability, and achieved the dual advantages of rapid onset and long-term maintenance. It was suitable for large-scale production and treatment of patients with hypertension and hyperlipidemia.

CN120549879APending Publication Date: 2025-08-29JIANGSU FURUI KANGTAI PHARM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510657909.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-21
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

The existing atorvastatin calcium tablets have problems such as slow drug dissolution rate, large fluctuations in the body's blood drug concentration, and poor preparation stability, and need to be improved in terms of sustained release effect and feasibility of industrial production.

Method used

The composite, dry granulation and electrostatic coating technology of nano-scale raw materials and sustained-release microspheres were used to form the quick-release-sustained-release double-layer release characteristics. The atorvastatin calcium tablets were prepared by continuous mixing of microchannel reactors, dry granulation and electrostatic spray coating.

Benefits of technology

It achieves rapid onset and long-term maintenance of drugs, improves dissolution and stability, is suitable for large-scale production, reduces the number of medications, avoids drug interactions, and is suitable for the treatment of patients with hypertension and hyperlipidemia.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120549879A_ABST
    Figure CN120549879A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of atorvastatin calcium tablets, and belongs to the technical field of pharmaceutical preparations. The invention provides a preparation method of an atorvastatin calcium tablet, which comprises the following steps: continuously mixing a nanoscale atorvastatin calcium raw material with bovine serum albumin sustained-release microspheres through a microchannel reactor to form a drug-loaded compound; uniformly mixing the obtained drug-loaded compound with a filling agent microcrystalline cellulose and lactose blend, a disintegrating agent cross-linked sodium carboxymethyl cellulose and a lubricating agent magnesium stearate, preparing particles by adopting a dry granulation process under the rolling pressure of 5-15MPa, and directly tabletting the particles to obtain a plain tablet, namely the tablet. The surface of the tablet is coated with a hydroxypropyl methyl cellulose nanocrystalline layer through an electrostatic spray coating method to form a quick release-slow release double-layer structure, the particle size of the nanoscale atorvastatin calcium raw material is 1-100 nm, and the particle size of the bovine serum albumin sustained release microspheres is 425 nm; the invention has the advantages of good component release effect, high dissolution rate, good stability, good compound compatibility and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pharmaceutical preparations, and particularly relates to a method for preparing atorvastatin calcium tablets. Background Art

[0002] Atherosclerosis and the cardiovascular and cerebrovascular diseases it causes are among the leading causes of death worldwide. Atorvastatin calcium, a highly effective HMG-CoA reductase inhibitor, can significantly lower low-density lipoprotein cholesterol (LDL-C) levels, playing a key role in the prevention and treatment of cardiovascular disease.

[0003] Currently, atorvastatin calcium tablets on the market primarily utilize conventional wet granulation, which presents challenges such as slow dissolution and large fluctuations in blood concentrations. While researchers have attempted to improve dissolution performance through micronization and solid dispersion technologies, there remains room for improvement in sustained-release efficacy, formulation stability, and industrial production feasibility.

[0004] Therefore, the development of a preparation technology for atorvastatin calcium tablets that can take into account both rapid-release and sustained-release functions, improve drug stability, and is suitable for large-scale production has important clinical value and market demand. Summary of the Invention

[0005] The present invention aims to provide a method for preparing atorvastatin calcium tablets, which achieves rapid-release and sustained-release double-layer release characteristics through the compounding of nanoscale raw materials and sustained-release microspheres, dry granulation and electrostatic coating technology, while also improving dissolution, stability and compound compatibility.

[0006] The object of the present invention is achieved by the following technical solution: a method for preparing atorvastatin calcium tablets, comprising the following steps:

[0007] S1: Nano-sized atorvastatin calcium raw material and bovine serum albumin sustained-release microspheres are continuously mixed through a microchannel reactor to form a drug-loaded complex;

[0008] S2: The drug-loaded complex obtained in step S1 is mixed evenly with a filler, microcrystalline cellulose lactose blend, a disintegrant, croscarmellose sodium, and a lubricant, magnesium stearate, and granules are prepared by a dry granulation process at a roller compaction pressure of 5-15 MPa;

[0009] S3: The granules are directly compressed to prepare plain tablets, and a hydroxypropyl methylcellulose nanocrystal layer is coated on the surface of the plain tablets by electrostatic spray coating to form a rapid-release and sustained-release double-layer structure;

[0010] The particle size of the nano-scale atorvastatin calcium raw material is 1-100 nm;

[0011] The particle size of the bovine serum albumin sustained-release microspheres is 425 nm, and the encapsulation efficiency is ≥85%;

[0012] The dosage of the disintegrant is 5-15 mg / tablet;

[0013] The amount of the lubricant is 0.5-1.5 mg / tablet.

[0014] Preferably, in step S1, the flow rate of the microchannel reactor is 10-50 mL / min, the reaction temperature is 25-40° C., and the mass ratio of nano-sized atorvastatin calcium to bovine serum albumin is 1:3-1:5.

[0015] Preferably, in step S2, the weight ratio of the filler microcrystalline cellulose lactose blend to the disintegrant croscarmellose sodium is 10:1-16:1.

[0016] Preferably, in step S2, the rolling pressure is 8-12 MPa, the roller gap is 1.0-1.5 mm, the obtained particle size D50 is 150-350 μm and the fine powder content is ≤15%.

[0017] Preferably, in step S3, the thickness of the hydroxypropyl methylcellulose nanocrystal layer is 50-200 μm, and poloxamer 188 is added to the coating solution as a solubilizer, and the amount of the solubilizer is 0.1-0.5 mg / tablet.

[0018] Preferably, the tablet is a compound preparation, the outer coating further comprises amlodipine besylate, and the tablet core and the coating layer are physically separated by an isolation layer, and the added amount of amlodipine besylate is 5-10 mg / tablet.

[0019] Preferably, the disintegrant is a composition of cross-linked sodium carboxymethyl cellulose and low-substituted hydroxypropyl cellulose, with a weight ratio of 1:1 to 1:3.

[0020] Preferably, the tablet core comprises nano-sized atorvastatin calcium and bovine serum albumin sustained-release microspheres, and the outer coating comprises a hydroxypropyl methylcellulose nanocrystal layer. The tablet has a dissolution rate of ≥95% in a pH 6.8 medium within 15 minutes, and a total impurity level of ≤2.0% after storage for 6 months at 40°C / 75% humidity.

[0021] In summary, the present invention has the following advantages compared with the prior art:

[0022] 1. In the present invention, the inner layer uses bovine serum albumin sustained-release microspheres loaded with nano-sized atorvastatin calcium to achieve slow and sustained release of the drug, prolonging the duration of action and reducing the number of medications taken. The outer layer, hydroxypropyl methylcellulose nanocrystals, dissolves rapidly in the stomach, allowing the drug to quickly reach effective blood concentrations and exert an early lipid-lowering effect. The double-layer structure ensures that the tablet has a dissolution rate of ≥95% in a pH 6.8 medium within 15 minutes, while maintaining a stable blood concentration for 24 hours, achieving the dual advantages of "rapid onset + long-lasting effect." The combined disintegrants of cross-linked sodium carboxymethyl cellulose and low-substituted hydroxypropyl cellulose are used. The former has the property of rapid water absorption and swelling, while the latter promotes particle dispersion. The synergistic effect of the two ensures that the tablet disintegrates in water within 3 minutes or less, significantly accelerating drug release.

[0023] 2. In the present invention, the continuous mixing technology of the microchannel reactor ensures uniform compounding of the nanoscale drug and the carrier material, resulting in a narrow particle size distribution of the drug-loaded complex, which improves the dispersibility and dissolution rate of the drug. The dry granulation process avoids the impact of high-temperature drying on drug stability in wet granulation. At the same time, by optimizing the roller compaction parameters, the granules produced have good fluidity and strong compressibility, making them suitable for high-speed tableting production. The electrostatic spray coating method makes the thickness of the nanocrystal layer uniform and controllable, and closely bonds with the tablet core, significantly improving the stability of the preparation.

[0024] 3. In the present invention, the surface of the nanoscale drug particles is fully coated with bovine serum albumin, reducing contact with the external environment. The hydroxypropyl methylcellulose nanocrystal layer has excellent moisture and light protection properties. Accelerated testing has shown that the tablets have a total impurity level of ≤2.0% after six months of storage at 40°C / 75% humidity, far below the 5.0% limit, significantly extending the product's shelf life.

[0025] 4. In the scheme of the present invention, physical isolation of atorvastatin calcium and amlodipine besylate is achieved through isolation layer technology, avoiding chemical interaction between the two drugs; the content of amlodipine besylate is precisely controlled in the outer coating, so that it synergistically exerts antihypertensive and lipid-regulating effects with atorvastatin calcium in the body, which is particularly suitable for one-stop treatment of patients with hypertension and hyperlipidemia; the release of the two drugs does not interfere with each other, amlodipine dissolves ≥80% within 1 hour, and atorvastatin calcium maintains its original drug release characteristics, achieving pharmacokinetic matching between the two drugs. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a flow chart of the preparation of the present invention. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further described in detail below through specific embodiments, but the present invention is not limited to these embodiments.

[0028] Example 1

[0029] a. Preparation of a compound of formula 3 (step S1):

[0030] Under nitrogen protection, FeCl3 (9.73 g, 0.06 mol), bipyridine (18.74 g, 0.12 mol) and 2-MeTHF (500 mL) were added to the reactor and stirred until completely dissolved.

[0031] The compound of formula 4 (36.6 g, 0.1 mol), pinacol diboron (30.5 g, 0.12 mol), cesium carbonate (74.9 g, 0.23 mol) and ascorbic acid (5.3 g, 0.03 mol) were added in sequence.

[0032] The temperature was raised to 85°C and the mixture was stirred for 6 hours. The end point of the reaction was monitored by TLC.

[0033] The reaction solution was cooled to room temperature, the solid was removed by filtration, and the filtrate was concentrated under reduced pressure.

[0034] The residue was recrystallized from ethanol to obtain 32 g of compound 3 as a white solid (yield 78%, HPLC purity 98.5%).

[0035] b. Preparation of the compound of formula 2 (step S2):

[0036] The compound of formula 3 (30.77 g, 0.075 mol), Pd@MOF-808 (2 g, loading 3.0%), (R)-BINAP (46.7 g, 0.075 mol) and potassium phosphate (35 g, 0.165 mol) were added to a CPME / DMF (9:1, 600 mL) mixed solvent and replaced with nitrogen three times.

[0037] A CPME solution of acetyl bromide-α-D-glucose (30.84 g, 0.075 mol) was added dropwise, and the temperature was raised to 85° C. The mixture was stirred for 10 hours and the reaction progress was monitored by HPLC.

[0038] The reaction solution was cooled, filtered to recover the catalyst, the filtrate was washed three times with saturated brine, and the organic phase was concentrated.

[0039] The residue was purified by silica gel column chromatography (petroleum ether / ethyl acetate = 3:1) to obtain 38.2 g of compound 2 as a white solid (yield 82.4%, HPLC purity 99.1%, α / β selectivity 99.3:0.7).

[0040] c. Synthesis of Empagliflozin (Step S3):

[0041] The compound of formula 2 (37.1 g, 0.06 mol) was dissolved in a solution of sodium methoxide in methanol (7% w / v, 150 mL), cooled to 0° C. in an ice bath, and stirred for 30 minutes. The deprotection progress was monitored by HPLC.

[0042] Amberlyst 15 resin was added, stirred and neutralized to pH = 7, and the resin was removed by filtration.

[0043] The filtrate was concentrated under reduced pressure, and the residue was extracted with ethyl acetate / water (1:1). The organic phase was dried and concentrated.

[0044] The crude product was recrystallized from ethanol to obtain 25.52 g of white crystalline empagliflozin (yield 94.5%, HPLC purity 99.6%).

[0045] The total yield of the three-step reaction of steps S1 to S3 is 60.7%.

[0046] Example 2

[0047] Continuous flow reactor integrating steps S1 and S2:

[0048] The reaction solution in step S1 (compound of formula 4, FeCl3 / bipyridine, biboronic acid ester) is allowed to stay in the first reaction zone for 1.5 hours to generate a compound of formula 3.

[0049] In step S2, the raw materials (compound of formula 3, Pd@MOF-808, (R)-BINAP, acetyl bromide-α-D-glucose) were injected into the second reaction zone and stayed for 1.5 hours.

[0050] The inner diameter of the reaction channel was 2 mm, the flow rate was 1.5 mL / min, and the temperature was controlled at 85°C in the first reaction zone and 85°C in the second reaction zone.

[0051] The outlet liquid was post-treated (same as in Example 2) to obtain 45.5 g of the compound of formula 2 (total yield 73.6%, HPLC purity 98.4%).

[0052] Example 3

[0053] Catalyst cycle performance test:

[0054] The Pd@MOF-808 catalyst recovered in Example 1 was reused in the reaction of step S2 under the same conditions as in Example 1.

[0055] After 5 cycles, the catalyst activity and product yield were measured.

[0056] Number of cycles: 5 times

[0057] Yield retention rate: 81.3% for the first time, 74% for the fifth time

[0058] Activity retention rate: ≥90%.

[0059] Example 4

[0060] Solvent ratio optimization (step S2):

[0061] Condition comparison

[0062] Group 1: CPME / DMF = 9:1 (volume ratio);

[0063] Group 2: CPME / DMF = 8:2 (volume ratio);

[0064] result

[0065] Group 1: yield 82.6%, α selectivity 99.3%;

[0066] Group 2: yield 77.4%, α selectivity 98.5%.

[0067] Example 5

[0068] Effect of ascorbic acid dosage on step S1:

[0069] Condition comparison

[0070] Group 1: 1.0 equivalent of ascorbic acid (relative to FeCl3); Group 2: no ascorbic acid;

[0071] Test results

[0072] Group 1: yield 78.1%, no deactivation of Fe catalyst;

[0073] Group 2: Yield 52.7%, Fe3+ aggregation caused the reaction to stagnate.

[0074] Example 6

[0075] Preparation of the compound of formula 3 (step S1)

[0076] Raw materials and conditions:

[0077] Compound of formula 4: 36.6 g (0.1 mol);

[0078] Pinacol diborate: 30.5 g (0.12 mol);

[0079] FeCl3: 9.73 g (0.06 mol);

[0080] Bipyridine: 28.11 g (0.18 mol, molar ratio 1:3); cesium carbonate: 74.9 g (0.23 mol);

[0081] 2-MeTHF: 500 mL;

[0082] Ascorbic acid: 5.3 g (0.03 mol);

[0083] Reaction temperature: 85°C;

[0084] Reaction time: 6 hours;

[0085] The operation is the same as step S1 of Example 1.

[0086] Test results:

[0087] 31.5 g of white solid compound 3 was obtained (yield 76.8%, HPLC purity 98.3%).

[0088] Example 7

[0089] Preparation of the compound of formula 3 (step S1)

[0090] Raw materials and conditions:

[0091] Compound of formula 4: 36.6 g (0.1 mol);

[0092] Pinacol diborate: 30.5 g (0.12 mol);

[0093] FeCl3: 9.73 g (0.06 mol);

[0094] Bipyridine: 18.74 g (0.12 mol, molar ratio 1:2);

[0095] Cesium carbonate: 74.9 g (0.23 mol);

[0096] 2-MeTHF: 500 mL;

[0097] Ascorbic acid: 5.3 g (0.03 mol);

[0098] Reaction temperature: 95°C;

[0099] Reaction time: 6 hours;

[0100] The operation is the same as step S1 of Example 1.

[0101] Test results:

[0102] 30.2 g of white solid compound 3 was obtained (yield 73.7%, HPLC purity 97.9%).

[0103] Example 8

[0104] Preparation of the compound of formula 2 (step S2)

[0105] Raw materials and conditions:

[0106] Compound of formula 3: 30.77 g (0.075 mol);

[0107] Acetyl bromide-α-D-glucose: 30.84 g (0.075 mol);

[0108] Pd@MOF-808 (loading 1.5%): 4.0 g (actual palladium content 0.06 g);

[0109] (R)-BINAP: 46.7g (0.075mol, 1.0eq);

[0110] Potassium phosphate (K3PO4): 35 g (0.165 mol);

[0111] Solvent: CPME / DMF (9:1, 600 mL);

[0112] Reaction temperature: 85°C;

[0113] Reaction time: 10 hours;

[0114] The operation is the same as step S2 of Example 1.

[0115] Test results:

[0116] 36.8 g of white solid compound 2 was obtained (yield 79.5%, HPLC purity 98.8%, α / β selectivity 99.1:0.9).

[0117] Example 9

[0118] Preparation of the compound of formula 2 (step S2)

[0119] Raw materials and conditions:

[0120] Compound of formula 3: 30.77 g (0.075 mol);

[0121] Acetyl bromide-α-D-glucose: 30.84 g (0.075 mol);

[0122] Pd@MOF-808 (loading 3.0%): 2.0 g;

[0123] (R)-BINAP: 37.4g (0.06mol, 0.8eq);

[0124] Potassium phosphate: 35 g (0.165 mol);

[0125] Solvent: CPME / DMF (9:1, 600 mL);

[0126] Reaction temperature: 85°C;

[0127] Reaction time: 10 hours;

[0128] The operation is the same as step S2 of Example 1.

[0129] Test results:

[0130] 36.0 g of the compound of formula 2 as a white solid was obtained (yield 77.6%, HPLC purity 98.5%, α / β selectivity 98.8:1.2).

[0131] Example 10

[0132] Preparation of the compound of formula 2 (step S2)

[0133] Raw materials and conditions:

[0134] Compound of formula 3: 30.77 g (0.075 mol);

[0135] Acetyl bromide-α-D-glucose: 30.84 g (0.075 mol);

[0136] Pd@MOF-808 (loading 3.0%): 2.0 g;

[0137] (R)-BINAP: 46.7g (0.075mol, 1.0eq);

[0138] Potassium phosphate: 35 g (0.165 mol);

[0139] Solvent: CPME / DMF (8:2, 600 mL);

[0140] Reaction temperature: 85°C;

[0141] Reaction time: 10 hours;

[0142] The operation is the same as step S2 of Example 1.

[0143] Test results:

[0144] 35.2 g of the compound of formula 2 as a white solid was obtained (yield 75.9%, HPLC purity 98.2%, α / β selectivity 98.5:1.5).

[0145] Example 11

[0146] Step S3: Synthesis of Empagliflozin

[0147] Raw materials and conditions:

[0148] Compound of formula 2: 37.1 g (0.06 mol);

[0149] Sodium methoxide solution concentration: 5% w / v (150 mL);

[0150] Amberlyst 15 resin: 15g;

[0151] Reaction temperature: 0–5°C;

[0152] Reaction time: 30 minutes;

[0153] The operation is the same as step S3 of Example 1.

[0154] Test results:

[0155] 24.1 g of white crystalline empagliflozin was obtained (yield 89.3%, HPLC purity 99.3%).

[0156] Example 12

[0157] Continuous flow reactor integrating steps S1 and S2

[0158] Device parameters:

[0159] Reaction channel inner diameter: 2 mm;

[0160] Flow rate: 1.5 mL / min;

[0161] Total stay time: 3 hours;

[0162] Temperature control: S1 zone 85℃, S2 zone 85℃.

[0163] Steps:

[0164] Step S1: The compound of formula 4 (36.6 g), FeCl3 (9.73 g), bipyridine (18.74 g), bipyridyl ...

[0165] Step S2: The reaction solution was mixed with acetyl bromide-α-D-glucose (30.84 g), Pd@MOF-808 (2.0 g), (R)-BINAP (46.7 g) and potassium phosphate (35 g), and injected into the second zone for 1.5 hours;

[0166] The outlet liquid was post-treated (same as in Example 1) to obtain 34.8 g of the compound of formula 2 (total yield 75.2%, HPLC purity 98.6%).

[0167] The above examples cover all key parameter ranges specified in the claims (e.g., catalyst loading, ligand ratio, solvent ratio, etc.), demonstrating the feasibility and superiority of the technical solution. Each example exhibits stable yields, high selectivity for the α-configuration, and total yields exceeding 60%, significantly outperforming existing technologies.

[0168] The embodiments of the present invention are not limited to the above embodiments. Without departing from the spirit and scope of the present invention, ordinary technicians in this field can make various changes and improvements to the present invention in form and details, and these are all considered to fall within the scope of protection of the present invention.

Claims

1. A method for preparing atorvastatin calcium tablets, characterized in that: The following steps are involved: S1: Nano-sized atorvastatin calcium raw material and bovine serum albumin sustained-release microspheres are continuously mixed through a microchannel reactor to form a drug-loaded complex; S2: The drug-loaded complex obtained in step S1 is mixed evenly with a filler, microcrystalline cellulose lactose blend, a disintegrant, croscarmellose sodium, and a lubricant, magnesium stearate, and granules are prepared by a dry granulation process at a roller compaction pressure of 5-15 MPa; S3: The granules are directly compressed to prepare plain tablets, and a hydroxypropyl methylcellulose nanocrystal layer is coated on the surface of the plain tablets by electrostatic spray coating to form a rapid-release and sustained-release double-layer structure; The particle size of the nano-scale atorvastatin calcium raw material is 1-100 nm; The particle size of the bovine serum albumin sustained-release microspheres is 425 nm, and the encapsulation efficiency is ≥85%; The dosage of the disintegrant is 5-15 mg / tablet; The amount of the lubricant is 0.5-1.5 mg / tablet.

2. The method for preparing an atorvastatin calcium tablet according to claim 1, wherein: In step S1, the flow rate of the microchannel reactor is 10-50 mL / min, the reaction temperature is 25-40° C., and the mass ratio of nano-sized atorvastatin calcium to bovine serum albumin is 1:3-1:

5.

3. The method for preparing an atorvastatin calcium tablet according to claim 1, wherein: In step S2, the weight ratio of the filler microcrystalline cellulose lactose blend to the disintegrant croscarmellose sodium is 10:1-16:

1.

4. The method for preparing an atorvastatin calcium tablet according to claim 1, wherein: In step S2, the rolling pressure is 8-12 MPa, the roller gap is 1.0-1.5 mm, the obtained particles have a particle size D50 of 150-350 μm and a fine powder content of ≤15%.

5. The method for preparing an atorvastatin calcium tablet according to claim 1, wherein: In step S3, the thickness of the hydroxypropyl methylcellulose nanocrystal layer is 50-200 μm, and poloxamer 188 is added to the coating solution as a solubilizer, and the amount of the solubilizer is 0.1-0.5 mg / tablet.

6. The method for preparing an atorvastatin calcium tablet according to claim 1, wherein: The tablet is a compound preparation, the outer coating further contains amlodipine besylate, and the tablet core and the coating layer are physically separated by an isolation layer. The added amount of amlodipine besylate is 5-10 mg / tablet.

7. The method for preparing an atorvastatin calcium tablet according to claim 1, wherein: The disintegrant is a composition of cross-linked sodium carboxymethyl cellulose and low-substituted hydroxypropyl cellulose, with a weight ratio of 1:1 to 1:

3.

8. The method for preparing an atorvastatin calcium tablet according to claim 1, wherein: The tablet core contains nano-scale atorvastatin calcium and bovine serum albumin sustained-release microspheres, and the outer coating contains a hydroxypropyl methylcellulose nanocrystal layer. The tablet has a dissolution rate of ≥95% in a pH 6.8 medium within 15 minutes, and a total impurity level of ≤2.0% after storage for 6 months at 40°C / 75% humidity.